2021
DOI: 10.1017/s0029665121001956
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients and sarcopenia: current perspectives

Abstract: Sarcopenia, a skeletal muscle disorder that is characterised by loss of muscle strength and mass, is common in older populations and associated with poorer health outcomes. Although the individual and economic costs of sarcopenia are widely recognised, current understanding of its pathophysiology is incomplete, limiting efforts to translate research evidence into effective preventive and treatment strategies. While nutrition is a key field of sarcopenia research, the role of differences in habitual diets, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 80 publications
0
13
0
2
Order By: Relevance
“…Interestingly, among the 13 vitamins for humans, vitamin D is the only one that has been extensively studied at both physiological and cellular levels. However, recent research suggests that other nutrients, such as antioxidants, manganese, vitamin A, vitamin E, and vitamin B6, also play a role in the prevention or improvement of sarcopenia [4,[7][8][9][10][11][12][13]. Recent human studies (2016-2021) in European countries as well as Japan have demonstrated that the low intake and low levels of vitamin B6 coexist with sarcopenia [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, among the 13 vitamins for humans, vitamin D is the only one that has been extensively studied at both physiological and cellular levels. However, recent research suggests that other nutrients, such as antioxidants, manganese, vitamin A, vitamin E, and vitamin B6, also play a role in the prevention or improvement of sarcopenia [4,[7][8][9][10][11][12][13]. Recent human studies (2016-2021) in European countries as well as Japan have demonstrated that the low intake and low levels of vitamin B6 coexist with sarcopenia [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no medical treatments for sarcopenia. In fact, the main recommendations for sarcopenia management are exercise and nutritional interventions [3,4]. Even though the role of nutrition in the prevention of sarcopenia forms a key field of research [5], extensive studies are still necessary to establish this fact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Обозначенные риски заболеваний и патологий обуславливают поиск современных способов адекватной коррекции нарушений метаболического статуса пациентов пожилого и старческого возрастов. Одним из таких направлений является восполнение суточной нормы потребления белка [7,8] Рекомендации по питанию для лечения и/или профилактики саркопении -возрастного атрофического дегенеративного изменения скелетной мускулатуры, -сформулированные Обществом саркопении, кахексии и истощения (SCWD), рекомендуют потребление белка не менее 1,0-1,5 г/кгМТ/день в сочетании с адекватными физическими упражнениями [9,10].…”
Section: аннотацияunclassified
“…Таким образом, для пациентов пожилого возраста необходимы специализированные рационы с набором определенных продуктов и с контролем не только калорийности, но и количественного и качественного состава белка. Это позволит повысить эффективность профилактических и лечебных мероприятий для данной категории пациентов [6,8,10]. Альтернативой должны выступать продукты с высокой долей содержания белка и благоприятными органолептическими и физикохимическими свойствами.…”
Section: аннотацияunclassified